The rule of law, arbitrariness and institutional virtue. (June 2019) - Thompson, Keith
This article summarises Professor Martin Krygier's work on the rule of law and his view that arbitrariness is its core and is under-theorised. From ancient philosophy, the author suggests that our rule of law settlement feels tentative because arbitrariness is a human characteristic that cannot be completely fixed with institutional checks and balances. The author observes that a variety of rule of law virtues are already expected of judicial decision-makers and suggests that these institutional virtues should be transferred into the administrative, executive and corporate decision-making space to advance the rule of law project.